Optical gap and fundamental gap of oligoynes and carbyne - Johannes Zirzlmeier (Nature Portfolio, 2020)
Carbyne, a linear sp-hybridized carbon allotrope, is synthetically inaccessible and its properties are extrapolated from those of defined oligomers. Here the authors analyze weak optical bands in two series of oligoynes and reassess the optical and fundamental gap of carbyne to lower values than previously suggested.